وقف المنافع في الفقه الإسلامي وتطبيقاته المعاصرة. - بيات, سعاد (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
الملخص: تناول البحث موضوع وقف المنافع في الفقه الإسلامي، وتطبيقاته المعاصرة، فكان الكلام عن مفاهيم وأحكام تتعلق بالوقف والمنافع، ثم طُرحت مسألة حكم وقف المنافع بين الفقهاء، مع الترجيح بين الآراء، كما تمّ سرد مجموعة من التطبيقات المعاصرة لوقف المنافع، منها: أوقاف رواق المغاربة بجامع الأزهر، ووقف الوقت، والوقف الرقمي. ومن النتائج المُتوصل إليها أن وقف المنافع: هو كل ما يكون محل الوقف فيه ليس له عين ملموسة، يمكن أن يساعد وقف المنافع في تجاوز بعض المشكلات التي تعاني منها مجموعة من المجتمعات العربية والإسلامية مثل وقف الوقت الذي يمكن أن يوفر باقة متنوعة من الخدمات مثل: رعاية كبار السن، والمرضى، والاعتناء باليتامى، ومساعدة الشباب المدمنين على التعافي، أوصى البحث بدعوة القانونيين إلى الاهتمام بالتشريع لوقف المنافع، وتهيئة البيئة القانونية له، وتسهيل إجراءات عقده؛ لتيسير وقفها، واستغلالها، والانتفاع بها. Résumé : فرنسية أو انجلزية Summary: The research dealt with the topic of Waqf benefits in Islamic jurisprudence, and its contemporary applications, so the talk was about concepts and provisions related to Waqf and benefits. Then the question of the ruling on the Waqf of benefits was raised among the jurists, with a preponderance between the opinions. A number of contemporary applications for the Waqf of benefits were also listed, including: Waqf of the Moroccan gallery(Riwaq al-Maghariba) at Al-Azhar mosque, Waqf of time, and digital Waqf. One of the conclusions reached is that the Waqf of benefits is everything that is the subject of the Waqf does not have a tangible eye. Waqf benefits can help overcome some of the problems experienced by a group of Arab and Islamic societies, such as Waqf time, which can provide a variety of services such as: caring for the elderly, the sick, caring for orphans, and helping young addicts recover. The research recommended inviting lawmen to pay attention to the legislation to Waqf the benefits, create the legal environment for it, and facilitate the procedures of its contract; to facilitate its cessation, exploitation, and benefit from it. Keywords: Waqf; benefits; Waqf time; Digital Waqf
أطوحة دكتوراه تخصص معاملات مالية معاصرة في العلوم الإسلامية
Keywords: الكلمات المفتاحية: الوقف؛ المنافع؛ وقف الوقت؛ الوقف الرقمي.; Waqf; benefits; Waqf time; Digital Waqf